AN ANALYSIS OF AMERICAN SLANGS AND IDIOM USED IN THE SHAWSHANK REDEMPTION MOVIE - Utama, Nofra; Erni, Erni; Syarfi, M (Universitas PGRI Sumatera Barat, 2024)
This study aims to identify and interpret various forms of slang and idioms that appear in film dialogue, as well as analyze their function and meaning in narrative and social contexts. The methodology used in this research is qualitative analysis with a descriptive approach. Dialogue in films is analyzed to identify examples of slang and idioms, which are then categorized by type, such as binomials, idiomatic phrases with verbs, and similes. In addition, the context of use of each expression is analyzed to understand how they contribute to the characterization and development of the plot. The research results show that the use of slang and idioms in